From DNA-protein interactions to the genetic circuit design using CRISPR-dCas systems - Shaytan, A. K.; Novikov, R. V.; Vinnikov, R. S.; Gribkova, A. K.; Glukhov, G. S. (Frontiers in Molecular Biosciences, 2022)
In the last decade, the CRISPR-Cas technology has gained widespread popularity in different fields from genome editing and detecting specific DNA/RNA sequences to gene expression control. At the heart of this technology is the ability of CRISPR-Cas complexes to be programmed for targeting particular DNA loci, even when using catalytically inactive dCas-proteins. The repertoire of naturally derived and engineered dCas-proteins including fusion proteins presents a promising toolbox that can be used to construct functional synthetic genetic circuits. Rational genetic circuit design, apart from having practical relevance, is an important step towards a deeper quantitative understanding of the basic principles governing gene expression regulation and functioning of living organisms. In this minireview, we provide a succinct overview of the application of CRISPR-dCas-based systems in the emerging field of synthetic genetic circuit design. We discuss the diversity of dCas-based tools, their properties, and their application in different types of genetic circuits and outline challenges and further research directions in the field.